Mathematics Phobia and Anxiety among Learners: Perspectives of Mathematics Teachers and Classroom Practices - Kumar, Amlesh; Behera, Laxmidhar (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics is an important subject with broad applicability to everyday life, yet often considered as a difficult subject for some learners. Mathematics phobia and anxiety are common phenomenon which have a negative impact on learning outcomes. Learners are not born with mathematics phobia and anxieties; they are victims to the educational processes. Learners think of mathematics as an extremely tough subject that they cannot be master over it. In this backdrop it was worth to the study the perspectives of mathematics teachers on factors influencing mathematics phobia and anxiety among learners at secondary stage. The study explores and analyses the perspectives of pre-service and in-service mathematics teachers on suggestive practices on eradication of fear of mathematics among learners. The study also reflects on the best practices performed by mathematics teacher for eradicating the mathematics phobia and anxiety among learners. Based on a descriptive survey research, the present study was confined to pre-service and in-service mathematics teachers of Bhubaneswar locality. Both quantitative and qualitative approaches have been used for collection of data. The tools included questionnaire for teachers (preservice and in service), classroom observation and case study protocol. Forty-three secondary level pre-service mathematics teachers and 5 in-service mathematics teachers of Bhubaneswar locality participated in the study. The major findings of this study revealed lack of confidence in performing mathematics/mathematical tasks, lack of courage to express their feelings about mathematics to their respective teachers, negative attitude towards mathematics, and avoidance of mathematics courses/classes, parental pressure, negative peer pressure etc. were the major factors influencing mathematics phobia and anxiety among learners at secondary stage. The study provided suggestive practices like to create learner friendly mathematics classrooms, individual attention on every learner by their teachers, use of different approaches and strategies in teaching mathematics among learners etc. to eradicate fear of mathematics among learners. The study also reflected on the evidence based practices performed by mathematics teacher like use of mathematics kit, use of community resources, relating mathematics to learners‘ prior experiences, providing ample scope for practices in mathematics instructions for eradicating the mathematics phobia and anxiety among learners. Based on the findings the study lists educational implications for teachers, students, parents and school board